Associação da região centromérica do cromossomo 14 com espessura de gordura em bovinos da raça Canchim - Veneroni, Gisele Batista (Universidade Federal de São Carlos, 2007)
Canchim is a synthetic breed that has been used in the beef cattle industry as an alternative for production intensification. However, this breed has poor fat deposition. Therefore researches have been done with the objective of increasing the fat deposition in this breed. These efforts include search for molecular markers that could aid the identification of animals with greater genetic potential for this trait. In several bovine populations the centromeric region of chromosome 14 was related with fat deposition. The thyroglobulin gene is located at 4.46 Mb in that chromosome and reports describe the influence of a polymorphism in the 5´ leader sequence of that gene on marbling and fat thickness. The scope of this work was to analyze the effect of this polymorphism in the thyroglobulin gene as well as of two flanking microsatellite markers, CSSM066 (2.95 Mb) and ILSTS011 (6.93 Mb) on backfat thickness of Canchim beef cattle. Five hundred and seventy two animals of two groups genetic (CA and MA), raised in two farms and pertaining to 64 half-sib families were evaluated. Associations of marker genotypes with phenotypic measures (backfat thickness) were analyzed by a mixed model. The results showed that microsatellite marker CSSM066 had a significant effect on fat thickness in the studied populations. However, this trait was not significantly associated with the polymorphism of the thyroglobulin gene and with the microsatellite marker ILSTS011, what suggests that another gene located in the centromeric region of chromosome 14 of bovine can be responsible for the variation on this trait. The genome region close to CSSM066 marker, that indicated association with fat thickness in our study, should be further investigated to produce information that may be incorporated in improvement programs
Keywords: Biologia molecular; Marcador molecular; Bovino de corte; Gordura subcutânea; Seleção assistida por marcadores - MAS; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL